Hubungan Pengetahuan Wanita Usia Subur tentang Kanker Mammae dengan Perilaku Pemeriksaan Payudara Sendiri di Desa Sumberejo Kecamatan Pabelan Kabupaten Semarang - Ninick Corea Fernandez; Isfaizah; Rini Susanti (Journal of Holistics and Health Science, 2020)
The prevalence of mammae cancer in Indonesia ranked second after cerviks cancer at 1.4 per 1,000 inhabitants, while in Semarang District the prevalence of mamame cancer ranked first with 112 cases. Prevention of cancer can be done by early detection with the method of breast examination itself (SADAR), but there are still many who do not know how to SADAR. The purpose of this researche is to analisis correlations between WUS knowledge about ca mammae with its own breast examination behavior (SADAR) in Sumberejo Village, Pabelan District.. Design observational analytical research with cross sectional approach. The population of this study is all women of childbearing age (WUS) in Sumberejo Village, Pabelan District, Semarang Regency. Sample as many as 100 WUS with Proportional Random Sampling sampling techniques. The research instrument is a questionnaire. Data analysis using univariate analysis with frequency distribution and bivariate analysis with chi-square test. Univariate analysis obtained most of WUS in Sumberejo Village Pabelan District Semarang District has enough knowledge about ca mammae by 43% and does not do SADAR by 65%. Bivariate analysis obtained there is a significant relationship between WUS knowledge about ca mammae and breast examination behavior itself (SADAR) (p =0.015). The better WUS knowledge of ca mammae the better wus behavior in breast examination itself. The need for socialization of SADAR examination for WUS as an effort to prevent the occurrence of cancer mamae. ABSTRAK Prevalensi kanker mammae di Indonesia menduduki peringkat kedua setelah kanker cerviks sebesar 1,4 per 1.000 penduduk, sedangkan di Kabupaten Semarang prevalensi kanker mamame menduduki urutan pertama sebesar 112 kasus. Pencegahan kanker mamaer dapat dilakukan dengan deteksi dini dengan metode pemeriksaan payudara sendiri (SADARI), namun masih banyak yang belum mengetahui cara SADARI. Tujuan penelirian ini untuk mengetahui pengetahuan WUS tentang ca mammae dengan perilaku pemeriksaan payudara sendiri (SADARI) di Desa Sumberejo Kecamatan Pabelan Kabupaten. Desain penelitian analitik observasional dengan pendekatan cross sectional. Populasi penelitian ini adalah seluruh wanita usia subur (WUS) di Desa Sumberejo Kecamatan Pabelan Kabupaten Semarang. Sampel sebanyak 100 WUS dengan teknik pengambilan sampel Proportional Random Sampling. Instrumen penelitian adalah kuesioner. Analisa data menggunakan analisis univariat dengan distribusi frekuensi dan analisis bivariate dengan uji chi-square. Analisis univariat didapatkan sebagian besar WUS di Desa Sumberejo Kecamatan Pabelan Kabupaten Semarang memiliki pengetahuan yang cukup tentang ca mammae sebesar 43% dan tidak melakukan SADARI sebesar 65%. Analisa bivariat diperoleh ada hubungan yang signifikan antara pengetahuan WUS tentang ca mammae dengan perilaku pemeriksaan payudara sendiri (SADARI) (p =0,015). Semakin baik pengetahuan WUS tentang ca mammae semakin baik perilaku WUS dalam pemeriksaan payudara sendiri. Perlunya sosialisasi pemeriksaan SADARI bagi WUS sebagai upaya pencegahan terjadinya kanker mamae.